Selling expert knowledge: The role of consultants in Singapore's new economy - Hans-Dieter Evers; Thomas Menkhoff (University of Bonn, Center for Development Research (ZEF), 2002)
In the emerging globalised knowledge society/economy, a group of professionals, namely experts and consultants gain in importance. The paper discusses the following issues: Who are these experts and consultants? Why is this group of knowledge workers strategically important and why is their importance socially in terms of number of persons and economically in terms of output or turnover growing? How can we explain the increasing professionalisation of consultants? How do they gain their expertise and which role does academic knowledge play in professional attainment? How do consultants package and apply expert knowledge? What are the challenges experts and consultants are facing in the new economy? Data from a survey of local consultancy firms are used to construct a profile of the Singapore consulting industry, their staff and their professional organisations. International consultants are more aggressive in advertising and selling their expertise than local consultants. They tend to distance themselves from academics as the producers of innovative knowledge, but stress their own experience. Finally we discuss the new situation under which consultants have to operate in the new economy.
Keywords: 330; International Development; Unternehmensberatung; Sachverständige; Wissensgesellschaft; Singapur; New Economy